2018
DOI: 10.1101/402750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limits to the rate of information transmission through MAPK pathway

Abstract: Two important signaling pathways of NF-κB and ERK transmit merely one bit of information about the level of extracellular stimulation. It is thus unclear how such systems can coordinate complex cell responses to external cues. Here, we analyze information transmission in the MAPK/ERK pathway that features relaxation oscillations and responds to EGF by pulses of activated ERK. Based on an experimentally verified computational model of the MAPK/ERK pathway, we demonstrate that when input sequences of EGF pulses … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…full timeseries) of NFkB into the dynamics of gene expression. It will be interesting to analyze what aspects of the dynamic patterns are more meaningful using either a features based approach [56] or through the use of information transmission rate [57].…”
Section: Plos Computational Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…full timeseries) of NFkB into the dynamics of gene expression. It will be interesting to analyze what aspects of the dynamic patterns are more meaningful using either a features based approach [56] or through the use of information transmission rate [57].…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…However, a high level of measurement error and a small sample size preclude an analysis of the reliability of information transmission accuracy from signaling dynamics into gene expression processes. Theoretical work on this question was more extensive [19,[55][56][57][58]. However past work based the analysis on specific dynamic features (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Information theory also provides a theoretical basis to move from phenomenological frameworks of dose-dependent gene responses that assumes continuous and graded control over gene expression levels, to thinking about true information transmission more rigorously. Interestingly, we and others (Billing et al, 2019;Cheong et al, 2011;Dubuis et al, 2013;Grabowski et al, 2019;Hansen and O'Shea, 2015;Harton and Batchelor, 2017;Jetka et al, 2019;Selimkhanov et al, 2014;Tkacik et al, 2009;Tudelska et al, 2017;Uda et al, 2013) have shown that these biological unit processes have relatively low information content of less than 1.5 bits (i.e. ~3 states).…”
Section: Discussionmentioning
confidence: 80%
“…This reliability is characterized by the noisiness of gene expression. Gene expression noise is an important and inherently stochastic process due to the low copy number of genes (Eldar and Elowitz, 2010;Elowitz and Leibler, 2000;Maheshri and O'Shea, 2007) and, together with cell-to-cell variability in general cellular components, creates a distribution of single-cell outputs for each unique input (Elowitz and Leibler, 2000;Grabowski et al, 2019;Gregor et al, 2007;Rosenfeld et al, 2005;Tkacik et al, 2009). As noise plays an important role in determining the reliability of a system and the fidelity of transmitted information, we first quantified how noise in our system was affected by F, A, and PW modulation.…”
Section: Single Cell Measurements Capture Total Population Noise (Figmentioning
confidence: 99%
“…Namely, the N50Y mutation of S gene significantly increases the force and number of interactions with the human receptor ACE2 [14,15]. The two aminoacid deletion at positions 69-70 in the same S gene leads to systematically biased diagnostic tests and doubles the reproductive advantage and numbers of the virus [16]. Furthermore, the P681H mutation of S protein might influence the cleavage of S protein through effest on S1/S2 subunits furin cleavage site [17].…”
Section: Resultsmentioning
confidence: 99%